2020
DOI: 10.3390/nu12113302
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD): An Update

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the first cause of chronic liver disease worldwide; it ranges from simple steatosis to steatohepatitis (NASH) and, potentially, cirrhosis and hepatocarcinoma. NAFLD is also an independent risk factor for type 2 diabetes, cardiovascular diseases, and mortality. As it is largely associated with insulin resistance and related disorders, NAFLD has been recently re-named as Metabolic dysfunction-Associated Fatty Liver Disease (MAFLD). At present, there are no approved ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 113 publications
2
99
1
1
Order By: Relevance
“…This result was in line with previous studies that the lower serum 25(OH)D level increased the risk of NAFLD [5,6]. Vitamin D may influence the development of MAFLD in both direct and indirect manners, including the impact on systemic and hepatic inflammation, the maintenance of insulin sensitivity, and the controlling microenvironment by suppressing adaptive immunity and up-regulating innate immunity [20]. The vitamin D supplementation can reduce liver steatosis and improve adipose tissue inflammation on animal model [21].…”
Section: Discussionsupporting
confidence: 91%
“…This result was in line with previous studies that the lower serum 25(OH)D level increased the risk of NAFLD [5,6]. Vitamin D may influence the development of MAFLD in both direct and indirect manners, including the impact on systemic and hepatic inflammation, the maintenance of insulin sensitivity, and the controlling microenvironment by suppressing adaptive immunity and up-regulating innate immunity [20]. The vitamin D supplementation can reduce liver steatosis and improve adipose tissue inflammation on animal model [21].…”
Section: Discussionsupporting
confidence: 91%
“…participates in the occurrence and development of chronic liver diseases [ 11 ]. Ding et al [ 12 ] conducted basic research on vitamin D receptor knockout mice and found that it could spontaneously produce liver injury and liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Significant reductions in serum alkaline phosphatase and GGT were observed with vitamin D and calcitriol supplementation from baseline levels; however, no beneficial effect was noted when comparing vitamin D, calcitriol, and placebo groups at the end of the study. Available data support the hypothesis of the potential benefits of vitamin D supplementation in selected populations of NAFLD patients, such as those with shorter disease duration and mild to moderate liver damage [45].…”
Section: Discussionmentioning
confidence: 68%